Pilot installation of a biosorption facility on a rice irrigation system - Suprun Veronika; Ustinova Viktoriya (Magazine of Civil Engineering, 2024)
The article presents the composition and design of the developed biosorption facility designed to purify drainage and waste water from rice irrigation systems. The object of the study is the Sarpin watering and irrigation rice System (SWIS) located in the semi-desert zone of the Republic of Kalmykia. The studies were conducted and tested in field and laboratory conditions. The composition of the biosorption facility should include at least four stages of purification. The main elements of the biosorption facility design are a settling tank (section 1), a filtration chamber filled with medium-sized crushed stone (20–40 mm) and NDP-600 diatomite powder (section 2), as well as a bioplateau complex (section 3) and a filter chamber with a mixture of sorbents (section 4). The parameters of the bioplateau were calculated and its design was improved by including dampers that provide the necessary contact time of the treated water with higher aquatic vegetation on a smaller area of the structure, increasing the efficiency of purification. A graphical model of the structure was created in the AutoCAD program. Also, the project of the biosorption facility module developed in AutoCAD made it possible to calculate the volume of earthworks and implement them on the SWIS in the Republic of Kalmykia.